Determinants of Demand Halal Food : A Bibliometric Analysis - Septiany Maulani Soraya; Fadli Agus Triansyah; Amir Machmud (Sekolah Tinggi Ekonomi dan Perbankan Islam Mr. Sjafruddin Prawiranegara, 2023)
This study aims to identify and analyze (1) the growth in the number of scientific publications in the field of halal food demand, (2) core journals, (3) researcher productivity; (4) number of documents based on institutional collaboration; (5) number of publications by subject/field; (6) publication development map based on keywords and author's name. Research using bibliometric method. Data was collected by searching through the Scopus database with the keywords demand for halal food in the category Article title, Abstract, Keywords in the period 1990-2021. Data were analyzed based on year, author, author's origin and subject using Microsoft Excel 2010. Meanwhile, the publication development map was analyzed using VosViewer software. The research results from this article itself found that Malaysia is the most contributing country regarding the topic of halal food demand with 81 documents and the most productive writer on the topic of Producer behavior is Iranmanesh with 4 documents. Originality This study is the first study to review and map halal food demand studies using bibliometric analysis, using data from year to year. All articles published in the journal have been reviewed in terms of methodology, country/case group and topics/subtopics for future research. Keywords: Demand, Halal Food, Bibliometric